Structurally controlled fluid flow: High-grade silver ore-shoots at Martha epithermal mine, Deseado Massif, Argentina - Paez, Gerardo Nestor (2011)
The role of structurally controlled fluid flow during epithermal ore-shoot formation is addressed through a structural study of the high grade Martha Mine epithermal deposit (Deseado Massif, Patagonia, Argentina). Martha is a silver-rich deposit, characterised by a complex mineralogy dominated by Ag–As–Sb sulphosalts and Cu–Pb–Zn sulphides. Mineralised veins can be subdivided into two groups: master structures that trend approximately NW–SE, and second-order structures that trend E–W and coalesce into the master structures. The Martha vein system is interpreted as a hard-linked step-over zone between two NW–SE trending fault segments. Furthermore, the geometry of ore-shoots at Martha Mine suggests a first-order structural control on their location and orientation. At the deposit scale, mineralisation is concentrated in the step-over zone. Mineralisation, and presumably hydrothermal fluid flow, was concentrated at the intersection between the two main vein groups. Finally, at the scale of single veins, jogs and subordinate step-overs were important channels for hydrothermal fluids and the formation of high-grade ore-shoots.